2008
DOI: 10.1124/dmd.108.020909
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiolic Acid as a Selective Cyclooxygenase-2 Inhibitory Component in Cannabis

Abstract: ABSTRACT:In the present study it was revealed that cannabidiolic acid (CBDA) selectively inhibited cyclooxygenase (COX)-2 activity with an IC 50 value (50% inhibition concentration) around 2 M, having 9-fold higher selectivity than COX-1 inhibition. In contrast, ⌬ 9 -tetrahydrocannabinolic acid (⌬ 9 -THCA) was a much less potent inhibitor of COX-2 (IC 50 > 100 M). Nonsteroidal anti-inflammatory drugs containing a carboxyl group in their chemical structures such as salicylic acid are known to inhibit nonselecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 31 publications
4
86
3
Order By: Relevance
“…Although we demonstrated for the first time that CBDA was a potent inhibitor of COX-2 (IC 50 = 2.2 M) purified from sheep placental cotyledons, which are a general enzyme source for screening (Cayman Chemical Company) (Takeda et al, 2008), a contradictory phenomenon, in which CBDA exhibited a very weak inhibitory potential on COX-2, was recently reported (Ruhaak et al, 2011). Since this research group and we used the same enzyme source, this discrepancy may have been caused by differences in the experimental conditions or purity of CBDA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we demonstrated for the first time that CBDA was a potent inhibitor of COX-2 (IC 50 = 2.2 M) purified from sheep placental cotyledons, which are a general enzyme source for screening (Cayman Chemical Company) (Takeda et al, 2008), a contradictory phenomenon, in which CBDA exhibited a very weak inhibitory potential on COX-2, was recently reported (Ruhaak et al, 2011). Since this research group and we used the same enzyme source, this discrepancy may have been caused by differences in the experimental conditions or purity of CBDA.…”
Section: Resultsmentioning
confidence: 99%
“…The specific use of the acidic cannabinoid as an active pharmaceutical ingredient has not yet been achieved because CBDA is recognized as the pharmacologically inactive form (Yamauchi et al, 1967;Razdan, 1986;Burstein, 1999). However, recent studies including ours demonstrated that, in addition to CBD, CBDA by itself exhibits biological actions, such as antibacterial effects (Appendino et al, 2008), the inhibition of cyclooxygenase-2 (COX-2) (Takeda et al, 2008), and anti-nausea/emetic effects (Bolognini et al, 2013;Rock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only a few in vivo investigations addressing cannabidiol's impact on COX-2 in cancer tissue showing no interference with COX-2 protein levels in experimental glioma (39) and colon cancer (40). About the impact of cannabinoids on COX-2 activity in cell-free assays, several cannabinoids including cannabidiolic acid (41), cannabigerol, and cannabigerolic acid (42) have been shown to profoundly inhibit COX-2, whereas cannabidiol tested at 100 mmol/L (41) or 300 mmol/L (42) failed to elicit such response or only slightly suppressed COX-2 at 100 mmol/L (39).…”
Section: Discussionmentioning
confidence: 99%
“…Further interactions can be predicted on the basis of the capability of both polyunsaturated endocannabinoid-like mediators and plant cannabinoids to inhibit, or to be oxidized by, cytochrome p450 oxygenases [55,56], which, in theory, allows the latter compounds, when administered systemically, to modulate the levels of the former. Finally, CBD acid, and much less so THC acid, were reported to inhibit cycloxygenase-2 [57], thus potentially inhibiting the formation not only of prostanoids, but also of prostamides and prostaglandin-glycerol esters. However, such interactions are yet to be demonstrated in vivo.…”
Section: Other Ways Through Which Non-thc Plant Cannabinoids Influencmentioning
confidence: 99%